A review of patient safety in Thailand and Malaysia - Yoelao, Dusadee; Mohan, Kanu Priya; Abd Hamid, Harris Shah (Behavioral Science Research Institute, Srinakharinwirot University, 2014)
This review explores the significance of patient safety in the two ASEAN nations of Thailand and Malaysia. It discusses the implications of upholding patient safety in the context of health care and also for developing medical tourism in both the countries. The relevance of human factors in patient safety is examined from the multi-level perspective of individuals, teams and organizations, and the overall health care systems. The article examines the research work in patient safety; with a discussion about the indigenous researches from both the countries. Further research areas are recommended that maybe of importance to both health care practitioners and researchers.